2010
DOI: 10.1111/j.1365-3180.2010.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resource availability on tolerance of herbivory in the invasive Alternanthera philoxeroides and the native Alternanthera sessilis

Abstract: Resource availability is known to affect herbivore selectivity and the ability of plants to respond to herbivores. However, little information is available for the performance of invasive plants subject to insect herbivory and limited resources availability. We conducted a glasshouse experiment using both the invasive Alternanthera philoxeroides and its native congener Alternanthera sessilis, to compare the effects of resource availability on plant tolerance to herbivory. The results suggest that water availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 28 publications
1
36
0
2
Order By: Relevance
“…Thus, I. capensis may be more tolerant of antagonism when soil nutrients are adequate; the reduced per-fl ower fl orivory due to higher fl ower production could also be considered a mechanism of tolerance to fl orivores. Soil nutrients, and nitrogen specifi cally, increase tolerance to leaf herbivory in many systems ( Wise and Abrahamson, 2008 ;Kohyani et al, 2009 ;Sun et al, 2010 ; but see Katjiua and Ward, 2006 ;Marshall et al, 2008 ;Suwa and Maherali 2008 ), but only one study has measured tolerance to fl oral antagonists (nectar robbers; Irwin, 2009 ), and there are no reports on the effects of abiotic factors on tolerance to fl oral antagonists. Increased plant growth and allocation to reproduction, both of which we see evidence for in this experiment, can serve as methods of tolerating herbivory in fertilized plots (e.g., Katjiua and Ward, 2006 ;Suwa and Maherali, 2008 ;Wise and Abrahamson, 2008 ;Kohyani et al, 2009 ;Sun et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, I. capensis may be more tolerant of antagonism when soil nutrients are adequate; the reduced per-fl ower fl orivory due to higher fl ower production could also be considered a mechanism of tolerance to fl orivores. Soil nutrients, and nitrogen specifi cally, increase tolerance to leaf herbivory in many systems ( Wise and Abrahamson, 2008 ;Kohyani et al, 2009 ;Sun et al, 2010 ; but see Katjiua and Ward, 2006 ;Marshall et al, 2008 ;Suwa and Maherali 2008 ), but only one study has measured tolerance to fl oral antagonists (nectar robbers; Irwin, 2009 ), and there are no reports on the effects of abiotic factors on tolerance to fl oral antagonists. Increased plant growth and allocation to reproduction, both of which we see evidence for in this experiment, can serve as methods of tolerating herbivory in fertilized plots (e.g., Katjiua and Ward, 2006 ;Suwa and Maherali, 2008 ;Wise and Abrahamson, 2008 ;Kohyani et al, 2009 ;Sun et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nowatzki and Weiss (1997) showed that feeding impacted canola seedlings more when grown in unstressed conditions compared with seedlings that experienced moisture stress. Similarly, Sun et al (2010) found the weed Alternanthera philoxeroides (Martius) Grisebach, had greater tolerance to herbivores when grown under moisture stress. The authors found A. philoxeroides roots grew faster in low moisture conditions and had a higher root:shoot biomass ratio than plants exposed to higher levels of moisture, suggesting a resource-allocation mechanism contributes to greater herbivory tolerance in droughtstressed plants.…”
Section: Discussionmentioning
confidence: 94%
“…Increase in snowfall or a change in snowfall variability is suggested to exacerbate the invasion of forbs in mixed-grass prairie ecosystem which in turn could influence the forage availability [22]. Soil moisture stress promoted greater herbivore tolerance for the invasive Alternan theraphiloxeroides and decreased it for the native congener A. sessilis [23].…”
Section: Precipitationmentioning
confidence: 99%